A Case of Primary T-Cell Central Nervous System Lymphoma: MR Imaging and MR Spectroscopy Assessment. (23rd May 2013) - Manenti, G.; Di Giuliano, F.; Bindi, A.; Liberto, V.; Funel, V.; Garaci, F. G.; Floris, R.; Simonetti, G.
Abstract : Primary central nervous system lymphomas (PCNSLs) are mainly B-cells lymphomas. A risk factor for the development of PCNSL is immunodeficiency, which includes congenital disorders, iatrogenic immunosuppression, and HIV. The clinical course is rapidly fatal; these patients usually present signs of increased intracranial pressure, nausea, papilledema, vomiting, and neurological and neuropsychiatric symptoms. PCNSL may have a characteristic appearance on CT and MR imaging. DWI sequences and MR spectroscopy may help to differentiate CNS lymphomas from other brain lesions. In this paper, we report a case of a 23-year-old man with T-primary central nervous system lymphoma presenting with a mass in the right frontotemporal lobe. We describe clinical, CT, and MRI findings. Diagnosis was confirmed by stereotactic biopsy of the lesion.